Ignition of Forest Combustible Materials by a Group of Crystallizing Metal Particles; Journal of Engineering Physics and Thermophysics; Vol. 93, iss. 3 - Baranovskiy N. V. Nikolay Viktorovich (2020, 2020)
Title screen